Preparation method of cobalt-based composite metal material and application of cobalt-based composite metal material in electrocatalytic urea oxidation

By using cobalt-based composite metal materials in electrocatalytic urea oxidation, the problems of high energy consumption and high cost of precious metal catalysts in traditional electrocatalytic technology are solved, and a high-efficiency and low-energy-consuming urea oxidation coupled hydrogen production reaction is achieved.

CN119877020AActive Publication Date: 2025-04-25FUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510190571.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-25
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

Traditional hydrogen evolution reactions and oxygen evolution reactions require high overpotentials, resulting in high energy consumption, and commonly used precious metal catalysts are costly and scarce, which limits the large-scale application of electrocatalytic hydrogen production.

Method used

The hydrothermal reaction of zinc acetate, cobalt acetate, cetyltrimethylammonium bromide and 2-methylimidazole is obtained to obtain the ZIF precursor of the cube interpenetrating structure, which increases the specific surface area of ​​the catalyst material, and obtains a cobalt-based composite metal material by adding ferrous chloride and low-temperature phosphation, thereby improving the activity of the electrocatalytic material.

Benefits of technology

It effectively reduces the overpotential of hydrogen produced by urea oxidation coupled with hydrogen, improves catalytic activity, and enhances the efficiency of electrocatalytic urea oxidation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877020A_ABST
    Figure CN119877020A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a cobalt-based composite metal material and application of the cobalt-based composite metal material in electrocatalytic urea oxidation. The preparation method comprises the following steps: carrying out a hydrothermal reaction on zinc acetate, cobalt acetate, cetyltrimethylammonium bromide and 2-methylimidazole to obtain a ZnCo-ZIF precursor, dissolving the ZnCo-ZIF precursor and ferrous chloride in methanol, stirring for a certain time, carrying out centrifugal washing and drying to obtain a FeZnCo-OH material, respectively placing the FeZnCo-OH material and sodium hypophosphite in a tubular furnace, and carrying out hydrothermal reaction on the FeZnCo-OH material and the sodium hypophosphite in the tubular furnace to obtain the FeZnCo-OH composite material. And introducing nitrogen, carrying out heating reaction, and cooling to room temperature to obtain the P-Fe2O3 / ZnCo2O4 material. The cobalt-based composite metal material can be applied to electrocatalytic urea oxidation, the electric potential is 1.3353 V when the current density is 10 mA cm <-2 > in 1.0 M KOH and 0.33 M urea solutions, and the cobalt-based composite metal material has excellent catalytic activity of urea oxidation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of transition composite metal materials and electrocatalysis, and specifically relates to a preparation method of a cobalt-based composite metal material and application of the same in electrocatalytic urea oxidation. Background Art

[0002] With the rapid development of human society and the improvement of human living standards, human demand for energy is also increasing. At present, global energy consumption is about 15 terawatts, and it is expected that this value will increase to 23 terawatts by 2030 and reach 30 terawatts by 2050. However, the limited reserves of fossil resources and the increasingly serious energy security, environmental pollution and climate change problems caused by the consumption of fossil resources will seriously affect the future life of human beings, so people are forced to vigorously develop new energy and renewable energy and optimize the existing energy structure. Hydrogen energy, as a clean, efficient, high calorific value and environmentally friendly sustainable secondary energy, is considered to be a promising energy carrier to meet our needs for future fuel applications.

[0003] Among various hydrogen production methods, electrocatalytic hydrogen production is considered to be a very promising technology with the advantages of high efficiency, cleanliness and high purity. However, the traditional hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) require a high overpotential, which will lead to a certain amount of energy consumption. In addition, among the common water electrolysis catalysts, Pt and Ru precious metals are often used as high-efficiency catalysts, but the high cost and scarce reserves of such catalyst materials have greatly hindered their large-scale application.

[0004] Transition metals such as Fe, Co, Ni, etc. and their sulfides, phosphides, nitrides, selenides or bimetallic heterojunctions and hydroxides are gaining more and more attention due to their superiority in electrocatalytic water decomposition and their easier availability compared to precious metals.

[0005] Based on this, the present invention proposes a method for preparing a cobalt-based composite metal material and its application in electrocatalytic urea oxidation. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems existing in the prior art and provide a method for preparing a cobalt-based composite metal material with simple preparation and high catalytic performance and its application in electrocatalytic urea oxidation. The present invention combines the electrocatalytic high efficiency performance of transition metals and the low potential characteristics of UOR hydrogen production, and obtains a ZIF precursor with a cubic interpenetrating structure through the hydrothermal reaction of zinc acetate, cobalt acetate, hexadecyltrimethylammonium bromide and 2-methylimidazole to increase the specific surface area of ​​the catalyst material. At the same time, it also increases the active sites of the electrocatalytic material by adding ferrous chloride, and obtains a cobalt-based composite metal material by low-temperature phosphating, further improving the catalytic activity of the electrocatalytic material in urea oxidation coupled hydrogen production, and effectively reducing the UOR overpotential.

[0007] To achieve the above object, the present invention adopts the following technical solution: A cobalt-based composite metal material, the preparation method of which comprises the following steps: (1) Dissolving zinc acetate, cobalt acetate, and hexadecyltrimethylammonium bromide in water to obtain solution A, and dissolving 2-methylimidazole in water to obtain solution B, mixing solution A and solution B and transferring them to a hydrothermal reactor for hydrothermal reaction, cooling to room temperature after the reaction, centrifuging, washing, and vacuum drying to obtain a ZnCo-ZIF precursor; (2) Dispersing the ZnCo-ZIF precursor and ferrous chloride tetrahydrate in methanol respectively, mixing and stirring for a certain period of time, centrifuging, washing, and vacuum drying to obtain FeZnCo-OH material; (3) The FeZnCo-OH material and sodium hypophosphite are placed at the two ends of a tubular calcining furnace respectively, calcined in a nitrogen atmosphere, cooled to room temperature, washed, and vacuum dried to obtain P-Fe2O3 / ZnCo2O4 material.

[0008] Furthermore, the molar ratio of zinc acetate, cobalt acetate and hexadecyltrimethylammonium bromide used in step (1) is 10:5:3-3.5.

[0009] Furthermore, the molar ratio of 2-methylimidazole to zinc acetate used in step (1) is 30:1.

[0010] Furthermore, the hydrothermal reaction conditions in step (1) are 120°C-140°C, and the reaction time is 8-12h.

[0011] Furthermore, the mass ratio of the ZnCo-ZIF precursor and ferrous chloride tetrahydrate used in step (2) is 1:2.

[0012] Furthermore, the stirring temperature in step (2) is 25° C., and the stirring time is 30-90 min.

[0013] Furthermore, the mass ratio of the FeZnCo-OH material and sodium hypophosphite used in step (3) is 1:5-10.

[0014] Furthermore, the calcination conditions described in step (3) are as follows: nitrogen is introduced, the temperature is increased to 300-350°C at a heating rate of 3°C-5°C / min, and the temperature is maintained for 2-3 hours.

[0015] Application of the cobalt-based composite metal material prepared by any of the preparation methods described above in electrocatalytic urea oxidation.

[0016] Furthermore, the above application method is as follows: placing a cobalt-based composite metal material on a glassy carbon electrode as a working electrode, a reference electrode as a Hg / HgO electrode, a counter electrode as a graphite rod electrode, and an electrolyte of 1.0M KOH and 0.33M urea solution.

[0017] The present invention combines the high-efficiency electrocatalytic performance of transition metals with the low-potential characteristics of UOR hydrogen production, obtains a ZIF precursor with a cubic interpenetrating structure through a hydrothermal reaction of zinc acetate, cobalt acetate, hexadecyltrimethylammonium bromide and 2-methylimidazole to increase the specific surface area of ​​the catalyst material, and at the same time, increases the active sites of the electrocatalytic material by adding ferrous chloride, and obtains a cobalt-based composite metal material through low-temperature phosphating, thereby further improving the catalytic activity of the electrocatalytic material in urea oxidation coupled hydrogen production and effectively reducing the UOR overpotential.

[0018] Compared with the prior art, the present invention has the following advantages: (1) In terms of type, the present invention proposes for the first time a cobalt-based composite metal material with a cubic interpenetrating structure; (2) From the perspective of raw materials, this is the first time that iron atom exchange and phosphating have been used to prepare cobalt-based composite metal materials; (3) From the application point of view, the present invention can effectively improve the efficiency of electrocatalytic urea oxidation coupled hydrogen production and reduce the overpotential. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope image of the ZnCo-ZIF precursor prepared in Example 1.

[0020] Figure 2 This is a scanning electron microscope image of the FeZnCo-OH material prepared in Example 1.

[0021] Figure 3 This is a scanning electron microscope image of the P-Fe2O3 / ZnCo2O4 material prepared in Example 1.

[0022] Figure 4 This is the X-ray diffraction pattern of the P-Fe2O3 / ZnCo2O4 material prepared in Example 1.

[0023] Figure 5 It is a comparison chart of LSV curves of materials prepared in Example 1 and Comparative Example 1 at UOR.

[0024] Figure 6 LSV curve of P-Fe2O3 / ZnCo2O4 material prepared in Example 1 in OER and UOR. DETAILED DESCRIPTION

[0025] A cobalt-based composite metal material, the preparation method of which comprises the following steps: (1) Dissolve zinc acetate, cobalt acetate, and hexadecyltrimethylammonium bromide in water at a molar ratio of 10:5:3-3.5 to obtain solution A, and dissolve 30 mmol of 2-methylimidazole in water to obtain solution B, wherein the molar ratio of 2-methylimidazole to zinc acetate is 30:1; mix solution A and solution B and transfer them to a hydrothermal reactor, the reaction temperature is 120°C-140°C, the reaction time is 8-12h, and after cooling to room temperature, centrifuge, wash, and vacuum dry to obtain a ZnCo-ZIF precursor; (2) Dissolving the ZnCo-ZIF precursor and ferrous chloride in methanol at a mass ratio of 1:2, mixing and stirring at a temperature of 25°C for 30-90 min, and then centrifuging, washing, and vacuum drying to obtain FeZnCo-OH material; (3) FeZnCo-OH material and sodium hypophosphite are placed at both ends of a tubular calcining furnace at a mass ratio of 1:5-10, and heated to 300-350°C at a heating rate of 3°C-5°C / min under a nitrogen atmosphere, and kept warm for 2-3 hours. After cooling to room temperature, the mixture is washed and vacuum dried to obtain P-Fe2O3 / ZnCo2O4 material.

[0026] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0027] Example 1 Preparation of ZnCo-ZIF precursor: 1mmol zinc acetate (Zn(CH3COO)2•2H2O), 0.5mmol cobalt acetate (Co(CH3COO)2•4H2O) and 0.33mmol hexadecyltrimethylammonium bromide (CTAB) were dissolved in 38ml deionized water to prepare solution A; 30mmol 2-methylimidazole was dissolved in 38ml deionized water to prepare solution B; solution A was quickly poured into solution B and stirred, then transferred to a Teflon reactor, reacted at 120°C for 12h, cooled to room temperature, centrifuged and washed three times with methanol and ethanol, and vacuum dried to obtain a purple ZnCo-ZIF precursor; Preparation of FeZnCo-OH material: 150 mg ZnCo-ZIF precursor was dissolved in 10 ml methanol and ultrasonicated for 15 min to obtain solution A; 300 mg ferrous chloride (FeCl2·4H2O) was dissolved in 15 ml methanol to obtain solution B. Solution B and solution A were mixed, stirred at 25°C for 60 min, then washed by centrifugation and vacuum dried to obtain brown-yellow FeZnCo-OH material; Preparation of P-Fe2O3 / ZnCo2O4 material: 30 mg of FeZnCo-OH material and 300 mg of sodium hypophosphite (NaH2PO2) were placed in the downstream and upstream of a tubular calcining furnace respectively, nitrogen was introduced and the temperature was increased to 350°C at a heating rate of 5°C / min, kept warm for 2 hours, cooled to room temperature, washed, and vacuum dried to obtain P-Fe2O3 / ZnCo2O4 material.

[0028] The P-Fe2O3 / ZnCo2O4 composite material obtained in Example 1 was characterized and tested as follows: Scanning electron microscopy (SEM): The scanning electron microscopy images of ZnCo-ZIF precursor, FeZnCo-OH material and P-Fe2O3 / ZnCo2O4 material are shown in Figure 2. Figure 1 , Figure 2 , Figure 3 As shown, the P-Fe2O3 / ZnCo2O4 composite material is a nanomaterial composed of interpenetrating cubic substances, which effectively increases the specific surface area and active sites.

[0029] X-ray diffraction (XRD): The X-ray diffraction pattern of P-Fe2O3 / ZnCo2O4 material is as follows Figure 4 As shown, the characteristic diffraction peaks of P-Fe2O3 / ZnCo2O4 material are 18.9°, 31.2°, 33.1°, 35.6°, 36.8°, 44.7°, 49.5°, 54.1°, 59.3°, 62.4°, 64.0°, 65.1°, and 72.3°, corresponding to the (1 0 4), (1 1 0), (0 2 4), (11 6), (2 1 4), (3 0 0), and (1 1 9) planes of Fe2O3 (PDF#86-0550), and the (1 1 1), (2 2 0), (3 1 1), (4 0 0), (5 1 1), (4 4 0) crystal plane, indicating that P-Fe2O3 / ZnCo2O4 has been successfully synthesized.

[0030] Comparative Example 1 Preparation of ZnCo-ZIF precursor: 1mmol zinc acetate (Zn(CH3COO)2•2H2O), 0.5mmol cobalt acetate (Co(CH3COO)2•4H2O) and 0.33mmol hexadecyltrimethylammonium bromide (CTAB) were dissolved in 38ml deionized water to prepare solution A; 30mmol 2-methylimidazole was dissolved in 38ml deionized water to prepare solution B; solution A was quickly poured into solution B and stirred, then transferred to a Teflon reactor, reacted at 120°C for 12h, cooled to room temperature, centrifuged and washed three times with methanol and ethanol, and vacuum dried to obtain a purple ZnCo-ZIF precursor; Preparation of FeZnCo-OH material: 150 mg ZnCo-ZIF precursor was dissolved in 10 ml methanol and ultrasonicated for 15 min to obtain solution A; 300 mg ferrous chloride (FeCl2·4H2O) was dissolved in 15 ml methanol to obtain solution B. Solution B and solution A were mixed, stirred at 25°C for 60 min, and then washed by centrifugation and vacuum dried to obtain brown-yellow FeZnCo-OH material.

[0031] The prepared ZnCo-ZIF precursor, FeZnCo-OH material and P-Fe2O3 / ZnCo2O4 material were used as working electrodes, the reference electrode was Hg / HgO electrode, the counter electrode was graphite rod electrode, the electrolyte was 1.0M KOH and 0.33M urea solution, the electrolyte volume was 40ml, and LSV test was carried out with a scan rate of 10mV / s. The experimental results are shown in Figure 5 As shown in the figure, it can be seen that the phosphating material can effectively reduce the potential of UOR. -2 The potentials of the three materials are 1.3601V, 1.3561V, and 1.3353V.

[0032] Example 2 Preparation of ZnCo-ZIF precursor: 1mmol zinc acetate (Zn(CH3COO)2•2H2O), 1mmol cobalt acetate (Co(CH3COO)2•4H2O) and 0.33mmol hexadecyltrimethylammonium bromide (CTAB) were dissolved in 38ml deionized water to prepare solution A; 30mmol 2-methylimidazole was dissolved in 38ml deionized water to prepare solution B; solution A was quickly poured into solution B and stirred, then transferred to a Teflon reactor, reacted at 120°C for 12h, cooled to room temperature, centrifuged and washed three times with methanol and ethanol, and vacuum dried to obtain a purple ZnCo-ZIF precursor; Preparation of FeZnCo-OH material: 150 mg ZnCo-ZIF precursor was dissolved in 10 ml methanol and ultrasonicated for 15 min to obtain solution A; 300 mg ferrous chloride (FeCl2·4H2O) was dissolved in 15 ml methanol to obtain solution B. Solution B and solution A were mixed, stirred at 25°C for 90 min, then washed by centrifugation and vacuum dried to obtain brown-yellow FeZnCo-OH material; Preparation of P-Fe2O3 / ZnCo2O4 material: 30 mg of FeZnCo-OH material and 300 mg of sodium hypophosphite (NaH2PO2) were placed in the downstream and upstream of a tubular calcining furnace respectively, nitrogen was introduced and the temperature was increased to 350°C at a heating rate of 5°C / min, kept warm for 2 hours, cooled to room temperature, washed, and vacuum dried to obtain P-Fe2O3 / ZnCo2O4 material.

[0033] Application Examples Application of P-Fe2O3 / ZnCo2O4 Composite Materials in Electrocatalytic Urea Oxidation 1. Application method 1) Add 4 mg of P-Fe2O3 / ZnCo2O4 composite material to a mixed solution of 30 μL Nafion and 2 ml of anhydrous ethanol, ultrasonically disperse for 30 minutes, and then drop 6 μL of the dispersion on a glassy carbon electrode to obtain an electrode material of the P-Fe2O3 / ZnCo2O4 composite material; 2) An AUTOLAB-302N electrochemical workstation was used, a three-electrode electrolytic cell was adopted as the electrolytic cell, the electrode material of the P-Fe2O3 / ZnCo2O4 composite material was used as the working electrode, the reference electrode was the Hg / HgO electrode, the counter electrode was the graphite rod electrode, the electrolyte was 1.0 M KOH and 0.33 M urea solution, and the electrolyte volume was 40 ml.

[0034] 3) LSV test: At a scan rate of 10 mV / s, the electrode material was tested for OER and UOR in 1.0 M KOH solution and 1.0 M KOH + 0.33 M urea solution, respectively. The electrode potential was referenced to the reversible hydrogen electrode (RHE): E RHE = E (Hg / HgO) +0.0591pH+0.098. The LSV curve test of OER and UOR of P-Fe2O3 / ZnCo2O4 composite material is shown in the figure Figure 6 As shown. When the P-Fe2O3 / ZnCo2O4 composite material was used for electrocatalytic urea oxidation, the current density reached 10 mA cm -2 The potential is 1.3353 V, indicating that UOR occurs preferentially over OER. By replacing OER, urea oxidation reaction can occur at a low potential, effectively reducing energy consumption.

[0035] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a cobalt-based composite metal material, characterized in that: The steps include: (1) Dissolving zinc acetate, cobalt acetate, and hexadecyltrimethylammonium bromide in water to obtain solution A, and dissolving 2-methylimidazole in water to obtain solution B, mixing solution A and solution B and transferring them to a hydrothermal reactor for hydrothermal reaction, cooling to room temperature after the reaction, centrifuging, washing, and vacuum drying to obtain a ZnCo-ZIF precursor; (2) Dispersing the ZnCo-ZIF precursor and ferrous chloride tetrahydrate in methanol respectively, mixing and stirring for a certain period of time, centrifuging, washing, and vacuum drying to obtain FeZnCo-OH material; (3) The FeZnCo-OH material and sodium hypophosphite are placed at the two ends of a tubular calcining furnace respectively, calcined in a nitrogen atmosphere, cooled to room temperature, washed, and vacuum dried to obtain P-Fe2O3 / ZnCo2O4 material.

2. The preparation method according to claim 1, characterized in that: The molar ratio of zinc acetate, cobalt acetate and hexadecyltrimethylammonium bromide used in step (1) is 10:5:3-3.

5.

3. The preparation method according to claim 1, characterized in that: The molar ratio of 2-methylimidazole to zinc acetate used in step (1) is 30:

1.

4. The preparation method according to claim 1, characterized in that: The hydrothermal reaction conditions in step (1) are 120°C-140°C, and the reaction time is 8-12h.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the ZnCo-ZIF precursor and ferrous chloride tetrahydrate used in step (2) is 1:

2.

6. The preparation method according to claim 1, characterized in that: The stirring temperature in step (2) is 25° C. and the stirring time is 30-90 min.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the FeZnCo-OH material and sodium hypophosphite used in step (3) is 1:5-10.

8. The preparation method according to claim 1, characterized in that: The calcination process in step (3) is to increase the temperature to 300-350°C at a heating rate of 3°C-5°C / min and keep the temperature for 2h.

9. A cobalt-based composite metal material prepared according to the preparation method according to any one of claims 1 to 8.

10. The use of the cobalt-based composite metal material in electrocatalytic urea oxidation according to claim 9, characterized in that: The cobalt-based composite metal material was placed on a glassy carbon electrode as a working electrode, the reference electrode was a Hg / HgO electrode, the counter electrode was a stone mill rod electrode, and the electrolyte was 1.0 M KOH and 0.33 M urea solution.

Citation Information

Patent Citations

  • Zn-doped CoP@MXene / NF composite material and synthesis method and application thereof

    CN114059093A

  • Preparation method for iron-cobalt phosphide / carbon composite material having layered structure, and button cell

    WO2023115503A1